(untitled) (Pesquisa Odontológica Brasileira, 2002)
Two methods of quantification of the biofilm (point-counting and planimetric) were tested and compared with the paper-weighing method and with the Prosthesis Hygiene Index. The internal surfaces of 62 complete dentures were stained and photographed. The slides were projected on a paper sheet. The total area and the area covered with biofilm were contoured using a black pencil. The point-counting method (experimental 1) was carried out on a mesh of equidistant points. For the planimetric method (experimental 2), the areas of interest were measured by means of a digital planimeter. In the paper-weighing method (control 1) the areas of interest were cut and weighed on a precision scale. In the determination of the Prosthesis Hygiene Index (control 2), the accumulation of biofilm was estimated by means of a scoring method. The results revealed an agreement rate of 82% between the paper-weighing method and the point-counting method, and an agreement rate of 95% between the former and the planimetric method, which was confirmed by high coefficients of correlation (0.98 and 0.99, respectively). The comparison with the Prosthesis Hygiene Index resulted in 55% of agreement with the point-counting method and in 37% of agreement with the planimetric method. The experimental methods can be useful in clinical studies involving the evaluation of the performance of denture cleansers.